Pendampingan Inovasi Kecerdasan Buatan dalam Pengembangan Asesmen Pembelajaran untuk Mendukung Literasi Digital bagi Guru SMP - Muhammad Ali Buchari; Sukemi Sukemi; Nabila Rizky Oktadini; Anna Dwi Marjusalinah; Ruth Helen Simarmata; Hasnan Afif (Jurnal Medika: Medika, 2025)
The Merdeka curriculum formulates learning that refers to the abilities needed in the era of industrial revolution 4.0 and society 5.0. The assessment is carried out as an effort to measure the level of achievement of learning indicators and collect information on student learning progress in various aspects.  Facts in the field show problems in implementing independent curriculum cognitive assessments in learning. This indicates the high need for preparing independent curriculum assessments, namely diagnostic assessments, formative assessments and summative assessments. Artificial intelligence or Artificial Intelligence (AI) is part of the industrial revolution 4.0 and society 5.0 so that integrating society and technology cannot be avoided.  Artificial Intelligence in mathematics learning has great potential to support learning effectiveness and efficiency. This service is a lecture activity that integrates artificial intelligence evaluation courses into service activities that are integrated with community service. This initiative was implemented to support digital literacy and increase teacher competency in utilizing modern technology, in accordance with the principles of the Independent Curriculum. This activity includes training, mentoring, and evaluation of the use of AI in learning assessment. As a result of this activity, teachers are able to understand the basic concepts of AI, innovation in assessment development, and its implementation in the classroom. Through various face-to-face and online meetings, this activity succeeded in providing new insights for teachers regarding the use of AI technology in learning, although there were challenges related to initial understanding and availability of supporting facilities. With intensive assistance, teachers are able to prepare assessments that are more adaptive and appropriate to student needs, so they are expected to be able to support improving the quality of education in the digital era.